Risk, Fate, Conciliation and Trust: An International Study of Attitudinal Differences Among Executives - Cummings, L. L.; Harnett, Donald L.; Stevens, O. J. (Academy of Management Journal, 1971)
In this study, data are reported comparing the beliefs of managers from five regional clusters (Greece, Spain, Central Europe, Scandinavia, and U.S.A.) on four basic attitudes (risk, self-determination, conciliation, and trust). The relative standings of the clusters are attitude specific, and the findings are compared to those of an earlier study by Haire, Ghiselli, and Porter. Only about 5 percent (which is significantly different from zero) of the total attitudinal variance is accounted for by regional grouping. Three additional factors are, therefore. examined in relation to attitudinal differences: (1) functional identification within a firm, (2) location within a single region, and (3) employment sector (private vs public) within a single country. The findings are interpreted within the context of a broad framework of possible causes of attitudinal differences across national groupings. Suggested implications for organizational practice are explicated with caution throughout the article.